Internationalisation of Finnish Public Research Organisation, Case: VTT Technology Studies - Rilla, Nina (My University, 2005)
Public Research Organisations have faced pressure of changes over the past few years. Challenges of internationalisation have increasingly become part of their everyday performance. Which- motives drive public research organisations to engage in international operations? What are the valid variables for assessing internationalisation in public research organisations? How do public research organisations internationalise? These are the main questions this study aims to answer. The theoretical framework is largely based on literature related to internationalisation of research and development. The discussion starts from introduction to branch in which public research organisations operate. Framework also provides a base for analysing motives and measures for public research organisation’s internationalisation. The empirical examination is carried out as a case study. A unit of public technical research organisation was analysed as a case study example. Two main data gathering techniques were used. A questionnaire, which was distributed among the employees of the case unit, provided primary data. Secondary data of the case organisation provided valuable information on certain issues. The analysis was based on both quantitative and qualitative examination. The results indicate public research organisation’s internationalisation motives to vary compared to motives of R&D intensive private companies. The motives related to researchers’ development of own knowledge and know-how are seen more important than for example acquirement of new customers. Belonging to networks and active participation is seen as a functional way of internationalisation for public research organisation. When analysing internationalisation of public research organisation, several other among financial variables can be found. The role of organisation and unit is to provide basis for individual researcher’s to internationalise rather than internationalise in itself.
Keywords: public research organisation; internationalisation; motives; variables; mode; market strategy; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|